(x-1)(x-2)(x-3)(x-4)=9/16
(x-2)(x-3) = х² - 5х + 6
(х - 1)(х - 4) = х² - 5 х + 4 = (х² - 5х + 6) - 2
[(х² - 5х + 6) - 2]·(х² - 5х + 6) = 9/16
(х² - 5х + 6)² - 2·(х² - 5х + 6) - 9/16 = 0
замена у = х² - 5х + 6
у² - 2у - 9/16 = 0
D = 4 + 9/4 = 25/4
√D = 5/2
y₁ = (2 - 5/2):2 = -1/4
y₂ = (2 + 5/2):2 = 9/4
возвращаемся к замене
1) х² - 5х + 6 = -1/4
х² - 5х + 25/4 = 0
D = 25 - 25 = 0
x = 5/2 = 2,5
2) х² - 5х + 6 = 9/4
х² - 5х + 15/4 = 0
D = 25 - 15 = 10
√D = √10
x₁ = (5 - √10):2 = 2,5 - √2.5 = √2.5 (√2.5 - 1)
x₂ = (5 + √10):2 = 2,5 + √2.5 = √2.5 (√2.5 + 1)
ответ: уравнение имеет два различных корня
x₁ = √2.5 (√2.5 - 1) и x₂ = √2.5 (√2.5 + 1)
и кратный корень
х₃ = х₄ = 2,5
3x+7y=35
5x=17+9y
x=(17+9y)/5=9y/5+17/5
7y+3(9y/5+17/5)=35
62y/5+51/5=35
62y/5=124/5
310y=620
y=620/310=2
5x-9*2=17
5x-18=17
5x=17+18=35
x=35/5
x=7
x=7, y=2
A=-2x+3y
A=-2*7+3*2
A=-14+6
A=-8